Interactivity: a factor to increase memorization - Rossi, George Bedinelli; Liveri, Fernanda; Da Silva, Dirceu; Garcia, Mauro Neves (Review of Business Management, 2012)
Today, approximately 29% of the world population use the Internet, against 38% in Brazil, which shows its importance in people’s routine not only in Brazil, but also worldwide. Being the Internet a communication media, this research evaluates the influence of Interactivity as a factor to increase memorization of Internet sites. According to literature, multiway, immediacy and contingency factors increase Interactivity and sites that provide one or more of these factors influence memorization. 20 in-depth personal interviews were conducted to improve the understanding the issue, to identify leads and elaborate our hypothesis, followed by a quantitative survey of 300 people. Hypotheses were tested using Chi-square and a hierarchical and non-hierarchical cluster analysis. Results showed that the smaller the number of leads of a specific website, the larger are its memorization and access. The theoretical contribution of this investigation is that websites that offer fewer leads are more interactive, which causes them to be remembered. The managerial implication is that websites with a clear position and a small quantity of information or leads tend to be more remembered and accessed by internet users. Key words: Interactivity. Memorization. Internet. Communication media.